Urban DNA and Sustainable Cities: A Multi-City Comparison - Votsis, Athanasios; Haavisto, Riina (Frontiers in Environmental Science, 2019)
The concept of urban DNA has been frequently utilized to describe how a set of urban growth parameters may encode the manner in which cities evolve in space and the spatial forms they assume as they do so. The five growth coefficients of the SLEUTH (Slope, Land-use, Exclusion, Urban, Transport, Hillshade) cellular automaton model of land use change and urban growth are often seen as an operationalization of urban DNA. For both theoretical urban studies and applied urban modelling, it is important to further develop this concept by understanding whether main urban DNA classes relate to distinct outcomes in terms of livability and sustainability. This study initiates this line of research by gathering empirical evidence about urban DNA and livability-sustainability indicators across a global sample of cities. It produces a behavioral taxonomy of cities according to their urban DNA and performance in livability and sustainability indices and indicators, and attempts a further link with the concept of urban commons. The results show that, notwithstanding variation across cities, it is possible to distinguish six such types of cities with relatively distinct behaviors and performances: multinodal, dispersed cities, with mixed outcomes (type A); multinodal, contiguous, slow-growing (type B); transport-oriented, dispersed, fast-growing (type C); large, buzzy, constrained (type D); dense, contiguous, fast-growing (type E); and transport-oriented, contiguous, interactive (type F) cities.